The Bible as a Network of Memes Analyzing a Database of Cross-References - Czachesz, István 1968- (2022)
This article puts forward the theory that the Bible is a network of cultural items (memes) that developed through an evolutionary process and has been transmitted for many centuries in a relatively stable form. Biblical cross-references reveal how the verses and passages of the Bible are connected into a network that is analogous to genetic networks in biology. The article presents a network model of cross-references, based on the Treasury of Scripture Knowledge. The article discusses the history of the database and the origin of the references; network statistics that yield insights into the history of the cross-references; node centrality statistics and the popularity of the respective verses in the history of Western biblical interpretation; and the modular structure of the network. The results are interpreted as tentative evidence for the collective behavior of populations in Western history being co-determined by a network of biblical memes.